Utility of Additional Tissue Sections in Genitourinary Specimen. (11th September 2019) - Hamza, Ameer; Alrajjal, Ahmed; Salehi, Sajad; Qu, Hong
Abstract: Objectives: Adequate sampling of surgical pathology specimens is vital to arriving at the correct pathologic diagnosis. To minimize sampling error and to establish an accurate pathologic diagnosis, pathologists use recuts and/or additional tissue sections (ie, more tissue sections in addition to initial representative sections). This study explores the utility of additional tissue sections in genitourinary specimen. Methods: Following institutional review board approval, we did a retrospective analysis of genitourinary pathology specimens received in our institution from 2012 to 2016 on which additional tissue sections were requested. A total of 59 specimens were identified. Results: Among total of 59 specimens, 23 (39%) were nephrectomy, 14 (23.7%) were orchiectomy, 13 (22%) were cystectomy/cystoprostatectomy, and 9 (15.3%) were adrenalectomy. Mean initial representative sections were 12.4 ± 4.1 in nephrectomy, 29.7 ± 13.7 in cystectomy/cystoprostatectomy, 9.1 ± 5.0 in orchiectomy, and 7.2 ± 3.4 in adrenalectomy specimens. Mean additional tissue sections were 9.0 ± 8.1 in nephrectomy, 19.5 ± 15.1 in cystectomy/cystoprostatectomy, 10.4 ± 7.3 in orchiectomy, and 10.6 ± 8.7 in adrenalectomy specimens. Significantly higher number of initial representative sections ( P < .0001) and additional tissue sections ( P = .02) were submitted in cystectomy/cystoprostatectomy specimens as compared to other specimens. Additional tissue sections proved useful in two nephrectomy specimens whereby renal vein invasion was identified; however, staging remained unchanged, and in one cystprostatectomy specimen whereby no residual was initially identified while on additional sampling, a focus of tumor was identified, changing the pathologic stage from ypT0 to ypT1. Conclusion: Renal vein is frequently undersampled in nephrectomy specimens. Cystectomy and cystoprostatectomy specimens are complex and require thorough sampling. If initial representative sections are deemed inadequate, additional tissue sections should be submitted to arrive at an accurate diagnosis.